2021
DOI: 10.1038/s41586-021-03910-8
|View full text |Cite
|
Sign up to set email alerts
|

An atlas of cortical arealization identifies dynamic molecular signatures

Abstract: The human brain is subdivided into distinct anatomical structures, including the neocortex, which in turn encompasses dozens of distinct specialized cortical areas. Early morphogenetic gradients are known to establish early brain regions and cortical areas, but how early patterns result in finer and more discrete spatial differences remains poorly understood1. Here we use single-cell RNA sequencing to profile ten major brain structures and six neocortical areas during peak neurogenesis and early gliogenesis. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
200
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 186 publications
(211 citation statements)
references
References 34 publications
(43 reference statements)
11
200
0
Order By: Relevance
“…Molecular signals within the cortex and those derived from extrinsic subcortical sources likely collaborate or compete with one another to generate molecular distinctions between cell types through developmental time. This diverse tapestry of transcriptional profiles may then underlie the presence of both discrete differences and continuous gradients of variation found between human cortical areas (Nowakowski et al, 2017;Li et al, 2018;Zhu et al, 2018;Bhaduri et al, 2021;Yao et al, 2021). This mixture of discrete and graded transcriptomic boundaries may be dynamic throughout development: interareal transcriptional states exhibit robust divergence prenatally, become more similar in infancy and childhood, and exhibit robust differences again in adolescence and onward (Li et al, 2018;Zhu et al, 2018).…”
Section: The Mechanisms Of Cortical Arealization Stem From Both Intrinsic and Extrinsic Signalingmentioning
confidence: 99%
See 4 more Smart Citations
“…Molecular signals within the cortex and those derived from extrinsic subcortical sources likely collaborate or compete with one another to generate molecular distinctions between cell types through developmental time. This diverse tapestry of transcriptional profiles may then underlie the presence of both discrete differences and continuous gradients of variation found between human cortical areas (Nowakowski et al, 2017;Li et al, 2018;Zhu et al, 2018;Bhaduri et al, 2021;Yao et al, 2021). This mixture of discrete and graded transcriptomic boundaries may be dynamic throughout development: interareal transcriptional states exhibit robust divergence prenatally, become more similar in infancy and childhood, and exhibit robust differences again in adolescence and onward (Li et al, 2018;Zhu et al, 2018).…”
Section: The Mechanisms Of Cortical Arealization Stem From Both Intrinsic and Extrinsic Signalingmentioning
confidence: 99%
“…More recent developmental and adult scRNA-seq studies have refined this theory, as the comparison of more cortical areas and the integration of molecular and connectivity profiles point to a continuum of cell types both within and across adult cortical areas. These studies have revealed that in both the developing and adult cortex, neighboring cortical areas have overlapping transcriptomic features that become increasingly distinct with greater spatial distance (Bhaduri et al, 2021;Yao et al, 2021). For example, the posterior-high to anteriorlow gradient marker gene NR2F1 is expressed at higher levels and in more cells in the posteriorly located V1 compared to the PFC (Bhaduri et al, 2021).…”
Section: Molecularly Defining Cortical Areas Via Transcriptomic Profilesmentioning
confidence: 99%
See 3 more Smart Citations